Uso do acervo de periódicos impressos da Biblioteca Comunitária da Universidade Federal de São Carlos: estudo de caso - Augusto, José Aparecido (Universidade Federal de São Carlos, 2016)
This study examines the use of collection of printed journals in paper Community Library (BCo) of the Federal University of São Carlos (UFSCar), campus San Carlos, through structured observational research, systematic and nonparticipating, fitting, academically, in large area "uses of information and collections", inspired in the intellectual contribution of Lancaster and other great authors in the field of user studies. The use of this collection of journals will also be analyzed by the survey, with the BCo, statistical usage data, in the period between the years 2012 to 2015. From the data obtained, it is expected to contribute to a possible establishment of parameters of a policy to readjust the space currently used by this collection of journals, aiming to collaborate with the academic community to be in tune with the lines of research and projects developed at the University.
Use of the collection of printed periodicals from the Community Library at the Federal University of São Carlos: a case study
Keywords: Estudo de usuários; Usos da informação e acervos; Periódicos impressos; Avaliação do uso da informação; Information user study; Print periodical collection; Information use evaluation; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA